1972
DOI: 10.1080/00445096.1972.11447448
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Behaviour and Feeding Habits of the Springbok,Antidorcas Marsupialis

Abstract: The stance and attitudes of the springbok are found to be similar to those of other gazelles. Gaits used are a rack-like walk (passgang), a trot and a gallop; display trot, the stott and the pronk are considered to be ritualised gaits of increa~ing intensity. Urination and defecation and comfort behaviour are described. Social behaviour is discussed and mixed herds, bachelor herds and solitary territorial males are shown to occur. Territorial marking is performed by taking up conspicuous positions, horn sweepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 7 publications
7
82
0
Order By: Relevance
“…In the Jack Scott Reserve, Transvaal, Mason (1976) found four males to be territorial for 4-11 months. There may be some evidence for increased territoriality during the rut, as suggested by Bigalke (1972), who also found that territoriality was not simply associated with mating. Assuming solitary males and single adult males accompanying female herds to be territorial, I recorded nearly 50% more territorial males during the rut (February-March), than during the lambing season (September).…”
Section: Time Spent On Territory By Malesmentioning
confidence: 68%
See 4 more Smart Citations
“…In the Jack Scott Reserve, Transvaal, Mason (1976) found four males to be territorial for 4-11 months. There may be some evidence for increased territoriality during the rut, as suggested by Bigalke (1972), who also found that territoriality was not simply associated with mating. Assuming solitary males and single adult males accompanying female herds to be territorial, I recorded nearly 50% more territorial males during the rut (February-March), than during the lambing season (September).…”
Section: Time Spent On Territory By Malesmentioning
confidence: 68%
“…As noted by Bigalke (1972) the springbok preorbital gland does not secrete and they do ·· not use glandular scent marks as a form of advertising. However, another form of scent marking is by means of dung and urine, which is regarded by Estes ( 1969) as the oldest form of territory demarcation.…”
Section: Territorial Advertisingmentioning
confidence: 99%
See 3 more Smart Citations